Faktor resiko gangguan pertumbuhan pada anak usia balita (1-5 tahun) di Rumah Sakit Ibu dan Anak (RSIA) Pucuk Permata Hati, Bali-Indonesia - Made Diah Ari Bestari; I Wayan Weta; Putu Aryani (Intisari Sains Medis, 2019)
Background: Impaired growth is still a problem that is encountered in children, so the search for factors related to growth disorders is important to evaluate in order to make an early anticipation.Method: This study used a case-control design conducted at Pucuk Permata Hati Child and Mother Hospital during the period February to April 2019. Sample search was done through consecutive methods. The search was carried out on the variables of child birth weight, maternal age at pregnancy, gestational age, hypertension conditions during pregnancy, history of abortion, maternal hemoglobin during pregnancy, placental disease (placental abruption or placenta previa), and breastfeeding. Data analysis using the help of SPSS version 25.0 software, chi-square test, logistic regression, and odds ratio calculation.Results: This study found that there was a significant relationship between maternal age â‰¤ 20 years, preterm pregnancy, hypertension during pregnancy, and placental disease during pregnancy as a risk factor that contributed to the occurrence of growth disorders in children (OR> 1; p <0.05). Then placental disease during pregnancy was the most important risk factor for growth disorders in children (aOR: 7.79; 95% CI: 1.79-75.97; p = 0.037).Conclusion: Age of preterm pregnancy, history of hypertension during pregnancy, and placental disorders are factors that play a role in the occurrence of growth disorders in children.